Georgia Architectural and Historic Properties Survey of Pavo [007] Harris St. Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Pavo [007] Harris St. Quitman, Ga. December 1980. A two story rectangular plan with gabled roof and shiplap siding. Filled in hip porch. Gabled dormer. Sash windows with 2/2 lights and 6/6 lights. Brick piers. Good condition. Date of Construction: c. 1910. Significant as part of a potential National Register historic district.
Georgia Architectural and Historic Properties Survey of Pavo [007] Harris St. Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.14 MB (1,204,116 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Quitman (Ga.)